Complications of Polydioxanone Foil Use in Nasal Surgery: A Case Series - Wang, Leo L.; Frankel, Andrew S.; Friedman, Oren (Facial Plastic Surgery, 2018)
Polydioxanone (PDS) foil is widely recognized as a septal cartilage replacement during rhinoplasties and is thought to be completely resorbable and biodegradable. Since its United States Food and Drug Administration approval in 2010, PDS foil has drawn significant enthusiasm and many surgeons consider it an ideal implantable biomaterial as reflected in numerous studies highlighting its benefits. However, scant literature exists highlighting relevant complications of PDS plates that may potentially lead to cavalier overuse. This descriptive case series assesses the outcomes of PDS foil usage in three patients seen for septoplasty at two independent institutions over the past 5 years. Our results demonstrate that PDS plate usage can lead to septal cartilage loss and resultant saddle nose deformıty associated with prolonged postoperative edema and inflammation. To our knowledge, this is the largest case series of this reported phenomenon.
Keywords: rhinoplasty; septoplasty; polydioxanone; biomaterials; nasal surgery